2021
DOI: 10.1186/s13063-021-05093-z
|View full text |Cite
|
Sign up to set email alerts
|

How effective are three methods of teaching oral hygiene for adolescents undergoing orthodontic treatment? The MAHO protocol: an RCT comparing visual, auditory and kinesthetic methods

Abstract: Background Fixed orthodontic appliances hamper oral hygiene procedures. The consequences are gingivitis and white spot lesions. Fifty to 70% of patients treated with braces encounter these problems. Their care in the USA represents an annual cost of five hundred million dollars. Initial education and motivation for oral hygiene depend on two categories of factors: firstly, practical prophylactic measures (instruments and medication, professional care) and secondly, the educational component: ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Fiberglass appears inferior compared to braided wire due to its increased thickness and the frequent delamination, which can end up being embarrassing [60]. The significance of patient support regarding effective oral hygiene maintenance should be well-established [103,104].…”
Section: Discussionmentioning
confidence: 99%
“…Fiberglass appears inferior compared to braided wire due to its increased thickness and the frequent delamination, which can end up being embarrassing [60]. The significance of patient support regarding effective oral hygiene maintenance should be well-established [103,104].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding plaque accumulation, we will use the modified plaque index (MPI) [ 66 ], since it allows to describe the amount of plaque not only in approximal areas like the approximal plaque index (API) [ 61 ], but also on the cervical area and around the bracket since additional plaque retention niches need to be evaluated in orthodontic patients and since probiotics reduced plaque accumulation [ 45 ]. To enable the reevaluation of the index and to ensure reproducibility, intraoral photographs [ 102 , 103 ] will be taken after staining of teeth. Since our study will focus on effects of fixed brackets, the GI [ 61 ], MPI [ 66 ] and PPD will be measured full-arch but only on teeth receiving fixed bonded orthodontic brackets.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study showed that in Group 3 the values of the plaque index were lower compared to the other patients, due to the impact that the video presentation had on them. 31 The hygiene of adult patients wearing fixed orthodontic appliances can also be improved by presenting images of the severe consequences of biofilm accumulation. 32,33 CONCLuSIONS 1.…”
Section: Discussionmentioning
confidence: 99%